Assessing fine particulate matter concentrations and trends in southern Ontario, Canada, 2003–2012 - K. Wayne Forsythe; Cameron Hare; Amy J. Buckland; Richard R. Shaker; Joseph M. Aversa; Stephen J. Swales; Michael W. MacDonald (AIMS Environmental Science, 2018)
Fine particulate matter is primarily released by transportation, residential and industrial processes. It can cause cardiopulmonary problems and has been attributed to the development of diabetes. Ontario is Canada’s most populous province and shares its southern border with the United States of America. The 2003 Canada-United States Border Air Quality Strategy outlines an initiative to reduce air pollution, specifically targeting southern Ontario due to its proximity to the U.S. and its historical air pollution levels. Ambient air concentrations of fine particulate matter (PM2.5) in southern Ontario were analyzed in this research. The data were obtained from the Ontario Ministry of the Environment. There are 40 stations across Ontario that monitor concentrations of up to six airborne pollutants on an hourly basis. The purpose of this research was to examine ambient air quality trends from 2003 to 2012 by generating prediction surfaces using the ordinary kriging spatial interpolation technique. Average PM2.5 levels for each year as well as maximum pollutant concentrations for the lowest and the highest year were produced. The results showed that fine particulate matter levels decreased, and the maximum levels per year also declined significantly. This indicates that fine particulate matter was greatly reduced and air quality generally improved in terms of PM2.5 during the analysis period.